Mao Zedong tongzhi, Zhou Enlai tongzhi, Liu Shaoqi tongzhi, Zhu De tongzhi zai yiqi
'Comrades Mao Tse-Tung, Zhou Enlai, Liu Shao-chi, and Zhu De together'. Place of persons f.l.t.r.: Zhu De, Zhou Enlai, Mao Tse-Tung, Liu Shao-chi. Printno. 8027.7565. See also BG E13/112, BG E11/113.